Development of sensory organs in the larvae of tiger grouper, Epinephelus fuscoguttatus - Lim, Leong Seng (2009)
Development of sensory organs in tiger grouper, Epinephelus fuscogttatus was examined by means of light- and scanning electron- microscopy, to provide useful information on their ecology and larval rearing. In newly hatched larvae, the eyes were not pigmented. The inner ears were oval-shaped vesicles with two otoliths. The larvae floated motionless in the water column. However, a pair of well developed free neuromasts was found behind the eyes, and the larvae were capable to avoid an approaching transparent pipette. In three-day-old larvae, the eyes were morphologically completed without rod cells and they commenced feeding on rotifers. The three semicircular canals of the inner ears, which play a role in the balance regulation, were completed, and the larvae were capable to swim horizontally. In 2o-ctay-old larvae, taste buds appeared in the buccal cavity, and they commenced feeding on Artemia nauplii. In 4O-day-old larvae, rod cells appeared and the inner ears were morphologically completed. The larvae started to settle down to the bottom of the tank. In SO-day-old fish, canal neuromasts formed and taste buds were found on the lips and breathing valves. At this stage, the fish commenced feeding on minced fish and stay at the bottom of the tank. In 6O-dayold fish, anterior and posterior olfactory pits were formed. Apparently, sensory organs of tiger grouper were well-developed when they settled to the bottom of the tank